2020
DOI: 10.1063/5.0013512
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium gate-controlled Josephson half-wave nanorectifier

Abstract: Recently, the possibility to tune the critical current of conventional metallic superconductors via electrostatic gating was shown in wires, Josephson weak-links, and superconductor-normal metal–superconductor junctions. Here, we exploit such a technique to demonstrate a gate-controlled vanadium-based Dayem nano-bridge operated as a half-wave rectifier at 3 K. Our devices exploit the gate-driven modulation of the critical current of the Josephson junction and the resulting steep variation of its normal-state r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 41 publications
3
32
0
Order By: Relevance
“…Recently, it has been shown that the superconducting (SC) properties of metallic Bardeen-Cooper-Schrieffer (BCS) superconductors can be influenced via electrostatic gating [1]. The most striking effect: reduction and suppression of the critical supercurrent, has been broadly demonstrated in metallic nanowires [2][3][4] and Dayem bridges [5][6][7][8] made of titanium, titanium nitrate, aluminum, niobium, and vanadium, as well as in aluminum-copper-aluminum Josephson junctions [9]. Moreover, recent experiments have probed the effect of electrostatic gating on the SC phase in a SQUID [10], and on the nature of the switching current distributions in gated titanium Dayem bridges [11].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that the superconducting (SC) properties of metallic Bardeen-Cooper-Schrieffer (BCS) superconductors can be influenced via electrostatic gating [1]. The most striking effect: reduction and suppression of the critical supercurrent, has been broadly demonstrated in metallic nanowires [2][3][4] and Dayem bridges [5][6][7][8] made of titanium, titanium nitrate, aluminum, niobium, and vanadium, as well as in aluminum-copper-aluminum Josephson junctions [9]. Moreover, recent experiments have probed the effect of electrostatic gating on the SC phase in a SQUID [10], and on the nature of the switching current distributions in gated titanium Dayem bridges [11].…”
Section: Introductionmentioning
confidence: 99%
“…The device shows a normal state resistance , a switching current at 2 K of mA, and a critical temperature K [ 31 ].…”
Section: Gate-driven Supercurrent Suppression In Nb and V Nanojuncmentioning
confidence: 99%
“…The bias current for this experiment was chosen to be μA to have a sharp super-to-normal transition and a linear dependence between R and . The continuous variation in the gate voltage provides continuous variation in junction resistance accordingly with the curves [ 31 ]. Due to the former behavior, the system is in the non-dissipative state for and a voltage-drop across the DB arises when the condition is satisfied.…”
Section: Gate-driven Supercurrent Suppression In Nb and V Nanojuncmentioning
confidence: 99%
See 2 more Smart Citations